Responses of testis, epididymis, and sperm of pubertal rats exposed to functionalized Multiwalled Carbon Nanotubes (2014)
The present study investigated the response of testes, epididymides and sperm in pubertal Wistar rats following exposure to 0, 0.25, 0.5, 0.75, and 1.0 mg kg21 functionalized multi-walled carbon nanotubes (f-MWCNTs) for 5 days. The results showed that administration of (f-MWCNTs) significantly increased the activities of superoxide dismutase, catalase, and glutathione peroxidase in a dose dependent manner in both testes and sperm compared with control group. Moreover, the significant decrease in the activity of glutathione-S-transferase and glutathione level was accompanied with significant elevation in the levels of hydrogen peroxide and malondialdehyde in both testes and sperm of (f- MWCNTs)-treated rats. The spermiogram of (f-MWCNTs)-treated rats indicated significant decrease in epididymal sperm number, sperm progressive motility, testicular sperm number and daily sperm production with elevated sperm abnormalities when compared with the control. Exposure to (f-MWCNTs) decreased plasma testosterone level and produced marked morphological changes including decreased geminal epithelium, edema, congestion, reduced spermatogenic cells and focal areas of tubular degeneration in the testes. The lumen of the epididymides contained reduced sperm cells and there was mild to severe hyperplasia epithelial cells lining the duct of the epididymis. Collectively, pubertal exposure of male rats to (f-MWCNTs) elicited oxidative stress response resulting in marked testicular and epididymides dysfunction.